Intelligent Hypothermia Care System using Ant Colony Optimization for Rules Prediction (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2017)
Intelligent Hypothermia Care System (IHCS) is an intelligence system uses set of methodologies, algorithms, architectures, and processes to determine where patients in a postoperative recovery area must be sent. Hypothermia is a significant concern after surgery. This paper utilizes the classification task in data mining to propose an intelligent technique to predict where to send a patient after surgery: intensive care unit, general floor or home. To achieve this goal, this paper evaluates the performance of decision tree algorithm, exemplifying the deterministic approach, against the AntMiner algorithm, exemplifying the heuristic approach, to choose the best approach in detecting the patient’s status. Results show the outperformance of the heuristic approach. The implication of this proposal will be twofold: in hypothermia treatment and in the application of ant colony optimization.